Electronic cigarettes - harmful substances contained in e-cigarette liquids and smoke - Białogłowski, Konrad; Giżewska, Kamila; Bochyński, Karol; Dacka, Michał; Dąbrowska, Paulina; Żuber, Michał; Molenda, Katarzyna; Borodziuk, Barbara; Borodziuk, Filip; Ciuba, Katarzyna (Quality in Sport, 2024)
Electronic cigarettes and electronic cigarette liquids are increasingly popular in society, especially among young people. However, despite the widespread belief that they are a safe alternative to traditional cigarettes, many scientific studies confirm that electronic cigarettes can be equally, if not more, harmful to health. There are many chemicals in electronic cigarette liquids, such as nicotine, propylene glycol, glycerol, flavors and fragrances. Some of these substances are toxic and can cause a number of negative health effects, such as irritation of the respiratory tract, the onset of lung disease, neurological disorders and increased risk of cardiovascular disease. In addition, electronic cigarettes can be harmful to the environment due to the emission of toxic substances into the air and improper disposal of used batteries. Therefore, an informed approach to the use of electronic cigarettes and an understanding of the potential health risks associated with them is necessary. Further scientific research and education of the public about the harms of electronic cigarettes are key to preventing the negative consequences associated with their use.